THE ROOTS OF MODERN POLITICAL SECULARISM AND ITS CRITIQUE - Muhammad Fajar Pramono; Bayu Sunarya (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2023)
Discussions about politics and human power, including discussions about the concept of the state, have been a discussion that has been going on since Greek times until the time of the growth of Islamic philosophy. The overemphasis on the power of reason led early modern Western societies to reject religion in all political discourse. At this stage, all views of man, power, the constitution, and the state eventually ceased to be associated with God. On the other hand, especially among Muslims, religion is still connected with discussions of politics and human power. This paper will reveal how secularization in political thought grew and developed through principles such as the state of nature and the social contract. Then, based on the thought of one of the influential Muslim scholars, Syed Muhammad Naquib Al-Attas, the author tries to provide a critique of the views of Western thinkers such as Thomas Hobbes, John Locke, and other philosophers, by presenting the concept of the ideal state form derived from the concept of tamaddun formulated by Al-Attas. This research is literature review research using the descriptive method. The findings of this research show that secularization is a product purely born by Western secular thinkers and not taken from any religious teachings, so Western political concepts cannot always be applied, especially in Muslim societies.